2016
DOI: 10.1159/000452924
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble Suppression of Tumorigenicity 2 Level Predicts All-Cause and Cardiovascular Mortality in Maintenance Hemodialysis Patients: A Prospective Cohort Study

Abstract: Background: Soluble suppression of tumorigenicity 2 (sST2) is a novel cardiovascular biomarker. This study aimed to evaluate the prognostic value of sST2 in hemodialysis patients. Methods: Four hundred and fourteen maintenance hemodialysis (MHD) patients were enrolled and followed up prospectively. Serum sST2 levels were measured. The endpoint was all-cause and cardiovascular mortality. Results: During a median follow-up of 22.3 months, 58 patients died, including 31 cardiovascular deaths. sST2 was an independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
(33 reference statements)
2
16
1
Order By: Relevance
“…In the heart, galectin-3 is linked to cardiac fibrosis, remodeling, and ventricular dysfunction 16, 38. In support of these mechanisms, clinical studies have reported an association of higher galectin-3 with all-cause mortality and cardiovascular mortality in patients with impaired kidney function 19 and those on hemodialysis 39, 40. Galectin-3 has been linked to the pathogenesis of several kidney diseases as well, including diabetic nephropathy, 41 infections, acute tubular necrosis, autosomal recessive polycystic kidney disease, renal cell carcinoma, lupus nephritis, and chronic allograft rejection 15 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the heart, galectin-3 is linked to cardiac fibrosis, remodeling, and ventricular dysfunction 16, 38. In support of these mechanisms, clinical studies have reported an association of higher galectin-3 with all-cause mortality and cardiovascular mortality in patients with impaired kidney function 19 and those on hemodialysis 39, 40. Galectin-3 has been linked to the pathogenesis of several kidney diseases as well, including diabetic nephropathy, 41 infections, acute tubular necrosis, autosomal recessive polycystic kidney disease, renal cell carcinoma, lupus nephritis, and chronic allograft rejection 15 .…”
Section: Discussionmentioning
confidence: 96%
“…Higher sST2 has also been linked to cardiac matrix remodeling 38 . Clinically, sST2 has been shown to predict heart failure, major cardiovascular events, and mortality independently48, 49, 50 and in association with other biomarkers and clinical characteristics in the general population17, 51 and among patients with kidney disease 39, 52. Fewer studies have examined the association of sST2 with kidney outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that ST2 was an independent prognostic factor and had a better prognostic ability than BNP in chronic hemodialysis patients 18 . In other study showing that ST2 is a predictor of all-cause and cardiovascular mortality in maintenance dialysis patients, ST2 showed no greater predictive power than BNP but showed greater predictive power when used with BNP 19 .…”
Section: Discussionmentioning
confidence: 82%
“…Multivariate Cox regression analysis reported by Obokata et al revealed that only sST2 was an independent risk factor for 2-year mortality when sST2 and NT-proBNP were included in the regression model simultaneously [7]. Another study demonstrated that the prognostic power of sST2 to predict 3year adverse clinical outcomes was weaker than that of NT-proBNP [8]. Apart from the discrepancy, neither of the two studies systematically investigated the prognostic value of the two biomarkers for short-term or long-term mortality in MHD patients; thus, the findings of our study may have an important impact on the clinical application of the two biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…The association of NT-proBNP with mortality in MHD has been shown by numerous studies [4,5]. Soluble suppression of tumorigenicity 2 (sST2) is a regulatory factor closely related to inflammation [6], and has been reported associated with mortality and fatal cardiovascular events in dialysis patients [7,8]. Moreover, circulating sST2 has been recommended as an additional risk stratification factor for acute and chronic heart failure by the American Heart Association [9].…”
Section: Introductionmentioning
confidence: 99%